Middle Miocene Climate and Stable Oxygen Isotopes in Europe Based on Numerical Modeling. Issue 10 (24th October 2022) - Botsyun, Svetlana; Ehlers, Todd A.; Koptev, Alexander; Böhme, Madelaine; Methner, Katharina; Risi, Camille; Stepanek, Christian; Mutz, Sebastian G.; Werner, Martin; Boateng, Daniel; Mulch, Andreas
Abstract: The Middle Miocene (15.99–11.65 Ma) of Europe witnessed major climatic, environmental, and vegetational change, yet we are lacking detailed reconstructions of Middle Miocene temperature and precipitation patterns over Europe. Here, we use a high‐resolution (∼0.75°) isotope‐enabled general circulation model (ECHAM5‐wiso) with time‐specific boundary conditions to investigate changes in temperature, precipitation, and δ 18 O in precipitation ( δ 18 Op ). Experiments were designed with variable elevation configurations of the European Alps and different atmospheric CO2 levels to examine the influence of Alpine elevation and global climate forcing on regional climate and δ 18 Op patterns. Modeling results are in agreement with available paleobotanical temperature data and with low‐resolution Middle Miocene experiments of the Miocene Model Intercomparison Project (MioMIP1). However, simulated precipitation rates are 300–500 mm/yr lower in the Middle Miocene than for pre‐industrial times for central Europe. This result is consistent with precipitation estimates from herpetological fossil assemblages, but contradicts precipitation estimates from paleobotanical data. We attribute the Middle Miocene precipitation change in Europe to shifts in large‐scale pressure patterns in the North Atlantic and over Europe and associated changes in wind direction and humidity. We suggest that global climate forcing contributed to a maximum δ 18 Op change of ∼2‰ over high elevation (Alps) and ∼1‰ over low elevation regions. In contrast, we observe a maximum modeled δ 18 Op decrease of 8‰ across the Alpine orogen due to Alpine topography. However, the elevation‐ δ 18 Op lapse rate shallows in the Middle Miocene, leading to a possible underestimation of paleotopography when using present‐day δ 18 Op —elevation relationships data for stable isotope paleoaltimetry studies. Key Points: A high‐resolution isotope‐enabled general circulation model is used to explore Middle Miocene climate and precipitation δ 18 O across Europe Middle Miocene bi‐directional precipitation change consistent with herpetological fossils and account for precipitation δ 18 O variations Global Miocene climate forcing contributed a max δ 18 O change of ∼2‰ over the high Alpine elevation and to ∼1‰ over low elevation